2021
DOI: 10.1590/s1677-5538.ibju.2020.0479
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of uro-oncological surgical treatment during the Sars-CoV-2 pandemic in a Brazilian tertiary oncology institution, the new world epicenter

Abstract: Introduction: The rapid spread of coronavirus disease 2019 (COVID-19) has dramatic effects on individuals and health care systems. In our institute, a tertiary oncologic public hospital with high surgical volume, we prioritize maintaining cancer treatment as well as possible. The aim of this study is to evaluate if uro-oncological surgeries at pandemic are safe. Materials and Methods: We evaluated patients who underwent uro-oncological procedures. Epidemiological data, information on COVID-19 infection related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
(20 reference statements)
0
2
0
1
Order By: Relevance
“…Initially, the biggest concern was about the risk of patients undergoing surgery to contract SARS-CoV-2, especially cancer patients. Anjos-Silva et al ( 79 ) reported that the longer the hospital stay after urological surgeries, the greater the risk of contracting COVID-19 and being a fatal case. It was considered that elective urological surgeries can be safe but that urgent cases need special care to avoid contamination.…”
Section: Discussionmentioning
confidence: 99%
“…Initially, the biggest concern was about the risk of patients undergoing surgery to contract SARS-CoV-2, especially cancer patients. Anjos-Silva et al ( 79 ) reported that the longer the hospital stay after urological surgeries, the greater the risk of contracting COVID-19 and being a fatal case. It was considered that elective urological surgeries can be safe but that urgent cases need special care to avoid contamination.…”
Section: Discussionmentioning
confidence: 99%
“…A rápida disseminação da doença de coronavírus 2019 , causada por um novo betacoronavírus conhecido como síndrome respiratória aguda grave coronavírus-2 (SARS-CoV-2), em todo o mundo, tem efeitos dramáticos em indivíduos e sistemas de saúde muito além daqueles infectados com SARS-CoV-2. A forte demanda por recursos, exacerbada pela capacidade limitada do sistema de saúde, significa que os sistemas de saúde ficaram rapidamente sobrecarregados e os hospitais se tornaram fontes de transmissão de vírus (Silva et al, 2021). O Brasil, bem como os demais países do mundo, tem se deparado com diversas mudanças decorrentes da pandemia do COVID-19.…”
Section: Introductionunclassified
“…Brazil and the world countries have been faced with many changes resulting from the COVID-19 pandemic. COVID-19 is a potentially serious respiratory infection caused by the coronavirus SARS-CoV-2 1,2 . Due to the high infection rate and severity of COVID-19, many governments have adopted measures to stimulate social distancing and some have even adopted lockdown policies 1,[3][4][5][6][7] .…”
Section: Introductionmentioning
confidence: 99%